Analysis of the factors affecting the students' choice of librarianship as a career - Espiritu, Maria Ana Corazon A.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
There is a continuous demand of librarians in every aspect of society: national, foreign, medical, law and information technology. Sadly, this demand cannot be addressed because of the very low supply being produced. Library schools and institutions cannot match up the work force with a few Library and Information Science graduates every year. This study aims to know some of the factors that affect students' choice of a career. The main objective of this study was to analyze the factors that affect the student's choice of librarianship as a career.
This study employed the normative study method. The respondents were third and fourth year students that are taking Bachelor of Library and Information Science from the following schools: Philippine Normal University, School of Library and Information Studies of the University of the Philippines, Centro Escolar University, University of the East, Polytechnic University of the Philippines and University of Santo Tomas.
The factor analysis revealed four components that affect the students' choice of librarianship as a career: Personal Interests, Abilities and Perceptions, People in the Librarianship Community, Personal and Family Aspirations and Global Aspirations. It is recommended though to add more specific factors for factor analysis and widen the scope of the sample to Greater Manila Area to further improve this study.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Vocational guidance -- Philippines -- Manila Metropolitan Area; Library science; Library schools -- Philippines -- Manila Metropolitan Area